Efficacy of traditional Chinese medicine nursing in stroke: a systematic review and meta-analysis - Yanling Chen; Hongyan Li; Zhe Wu; Mingyuan Jiao (Frontiers in Neurology)
ObjectiveSome clinical studies have suggested that traditional Chinese medicine (TCM) nursing techniques may promote better recovery in stroke patients compared to conventional neurological nursing. However, high-quality evidence-based research is still lacking. This study selected two outcome indicators—motor function and activities of daily living (ADL)—to systematically evaluate the efficacy of TCM nursing techniques in the rehabilitation of stroke patients.MethodsSeven major Chinese and English databases were systematically searched. The Fugl-Meyer Assessment (FMA) and the Modified Ashworth Scale (MAS) were used to evaluate motor function, while the Barthel Index (BI) was used to assess ADL. Subgroup analyses were conducted based on study characteristics to explore potential sources of heterogeneity.ResultsA total of 18 studies involving 1,419 patients were included. Meta-analysis results showed that, compared with conventional care, the TCM nursing group demonstrated significantly better outcomes in FMA (SMD = 1.92, p = 0.0066), MAS (SMD = −0.82, p = 0.0416), and BI (SMD = 1.34, p < 0.0001). Meta-regression and subgroup analyses indicated that nursing model, stroke type, and risk of bias were not sources of heterogeneity.ConclusionCompared to conventional care, TCM nursing techniques can significantly improve spasticity in stroke patients, and also provide some benefits for limb motor function and ADL. Given the high heterogeneity and poor GRADE assessment of FMA and BI, the above results should be interpreted with caution.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251006204.